Rancang Bangun Sistem Informasi Penilaian Kinerja Keuangan pada PT WIJAYA KARYA GEDUNG - Kurniawan, Donny; Tanuwijaya, Haryanto; Arifin, Mochammad (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract: PT Wijaya Karya Gedung is one of subsidiaries of PT Wijaya Karya, which business focus on apartments, private buildings, offices, condominium hotels, educational facilities, and many other commercial buildings. Currently in the company there are difficulties for assessing financial performance based on the Ministerial Decree No. KEP-100 / MBU / 2002, because during this financial performance assessment the system is not able to provide details of the assessment and just only issued a single value. As a result, companies cannot know the financial position in detail.Given these problems, then the assessment information system created financial performance at PT Wijaya Karya Gedung is able to provide details of the financial assessment in detail using SDLC which refers to the Decree of the Minister for State Owned Enterprises No. KEP-100 / MBU / 2002.Based on testing, the application can perform the calculation of financial performance which refers to the Decree of the Minister for State Owned Enterprises No. KEP-100 / MBU / 2002. Applications can also generate reports COA, reports the weight, the weight indicator reports, and financial performance assessment reports. Keywords: Performance Assessment, Information System, State-Owned Enterprises